2008
DOI: 10.1007/s10532-008-9176-4
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of pyridine by an isolated bacterial consortium/strain and bio-augmentation of strain into activated sludge to enhance pyridine biodegradation

Abstract: Pyridine and pyridine based products are of major concern as environmental pollutants due to their recalcitrant, persistent, toxic and teratogenic nature. In this study, we describe biodegradation of pyridine by an isolated consortium/strain under aerobic condition. Batch experiment results reveal that at lower initial pyridine concentrations (1-20 mg l(-1)), almost complete degradation was observed whereas at higher concentration (30-50 mg l(-1)), the degradation efficiency was dropped significantly. This may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…This high rate of degradation may be attributed to cultivation of the granules at a phenol concentration of 500 mg L -1 [1]. Pyridine biodegradation by an isolated consortium in the concentration range of 1-20 mg L -1 is reported [18] wherein the authors have evaluated the growth kinetics and have derived kinetic constant values for the isolated consortium viz. Y: 0.155 g biomass/g pyridine, l max : 0.5088 day -1 and K d : 0.132 day -1 .…”
Section: Discussionmentioning
confidence: 99%
“…This high rate of degradation may be attributed to cultivation of the granules at a phenol concentration of 500 mg L -1 [1]. Pyridine biodegradation by an isolated consortium in the concentration range of 1-20 mg L -1 is reported [18] wherein the authors have evaluated the growth kinetics and have derived kinetic constant values for the isolated consortium viz. Y: 0.155 g biomass/g pyridine, l max : 0.5088 day -1 and K d : 0.132 day -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Pyridine and pyridine based products are of major concern as environmental pollutants due to their recalcitrant, persistent, toxic and teratogenic nature. Lodha et al (2008) have studied the biodegradation of pyridine by an isolated consortium/strain under aerobic condition. Batch experiment results revealed that at lower initial pyridine concentrations (1-20 mg/l), almost complete degradation was observed whereas at higher concentration (30-50 mg/l), the degradation efficiency was dropped significantly.…”
Section: Microbial Consortia For Bioremediationmentioning
confidence: 99%
“…Most of these studies were concentrated on the isolation and characterization of pyridine-degrading microorganisms [10,11], bioaugmentation of the bioreactors by adding pyridine-degrading microorganisms [11][12][13], immobilization of the microorganisms capable of degrading pyridine [14,15], and so on. However, considering the nauseating odour at aerobic condition, pyridine degradation under anaerobic or anoxic condition has attracted increasing interest in recent years [16].…”
Section: Introductionmentioning
confidence: 99%